ANALISIS ECONOMIC VALUE ADDED SEBAGAI ALAT UNTUK MENGUKUR KINERJA KEUANGAN PADA PT. NIPPON INDOSARI CORPINDO TBK YANG TERDAFTAR DI BEI PERIODE 2014-2018 - Ika Wahyuni; Dwi Perwitasari Wiryaningtyas; Siti Faika (Relawan Jurnal Indonesia, 2019)
This study aims to assess the financial performance of PT. Nippon Indosari Corpindo Tbk in the 2014-2018 period used Economic Value Added Analysis. Data analysis methods used in this research are Net Operating Profit After Tax, Invested Capital, Weighted Average Cost of Capital, Weighted Capital Cost, and Economic Value Added. The results of the study using Economic Value Added Analysis shows that Economic Value Added at PT. Nippon Indosari Corpindo Tbk during the past period experienced fluctuations in 2014 amounting to Rp70,191,382,851, an increase in 2015 of Rp 112,678,462,412 and decreased in 2016 amounting to Rp101,793.508,446, then decreased again in 2017 and 2018 amounting to Rp 99,383,770,798 and Rp 19,837,411,622. The value of EVA in EVA companies is > 0, which means that the company has created added value for the company even though each year the research experiences ups and downs of the EVA's value. Economic value added in this case the company in measuring economic profit has been fulfilled. Economic Value Added generated by companies can be considered healthy and positive value even though each year the research has fluctuated